2021
DOI: 10.12688/f1000research.51094.1
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Ziprasidone induced neuroleptic malignant syndrome

Abstract: Neuroleptic malignant syndrome (NMS) is a well-recognized neurologic emergency. It presents with classic features including hyperthermia, autonomic instability, muscle hypertonia, and mental status changes. The syndrome is potentially fatal and is associated with significant morbidity due to complications such as rhabdomyolysis, acute kidney injury, and ventricular arrhythmias due to the trans-cellular electrolyte shift. NMS is conventionally associated with the first-generation antipsychotic agents, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The physical conditions of trauma patients were relatively severe compared with those with other diseases. The major reason for drug administration was postoperative restlessness, 18,19,25,27,28,[30][31][32][33][34][36][37][38][39]44,46,[52][53][54][55][57][58][59][61][62][63][64][67][68][69][70]72,75,78,81,84,86,89 followed by nausea 19,22,24,33,42,51,55,59,61,73,80,86 and delirium 35,…”
Section: Occurrences Of Nms In Fields Other Than Psychiatrymentioning
confidence: 99%
See 2 more Smart Citations
“…The physical conditions of trauma patients were relatively severe compared with those with other diseases. The major reason for drug administration was postoperative restlessness, 18,19,25,27,28,[30][31][32][33][34][36][37][38][39]44,46,[52][53][54][55][57][58][59][61][62][63][64][67][68][69][70]72,75,78,81,84,86,89 followed by nausea 19,22,24,33,42,51,55,59,61,73,80,86 and delirium 35,…”
Section: Occurrences Of Nms In Fields Other Than Psychiatrymentioning
confidence: 99%
“…We performed a review of NMS case reports from clinicians other than psychiatrists in English and Japanese literature. They could be classified into two groups: (1) cases in which NMS onset was triggered by administering causative drugs 17–19,22–89 and (2) cases in which NMS developed from disruption of regular medication (Tables 7 and 8). 8,16,90–114 An example of the former is a case in which antipsychotic drugs were administered for postoperative delirium; an example of the latter is a case in which regular medication (i.e., antipsychotic drugs) to treat schizophrenia was discontinued temporarily because of general anesthesia.…”
Section: Occurrences Of Nms In Fields Other Than Psychiatrymentioning
confidence: 99%
See 1 more Smart Citation
“…Prakash et al also concluded from an in vitro study using human liver microsomes that co‐administration of ZIPR with other CYP substrates is not expected to lead to clinically relevant pharmacokinetic interactions 21 . Other potentially life‐threatening complications following ZIPR usage include neuroleptic malignant syndrome and drug reaction with eosinophilia and systemic symptoms (DRESS), which have been reported in at least seven and three cases (US data only), respectively, none of which resulted in death 22–24 . Other adverse side effects include somnolence, respiratory tract infections, dizziness, and movement disorders 2…”
Section: Introductionmentioning
confidence: 99%
“…21 Other potentially lifethreatening complications following ZIPR usage include neuroleptic malignant syndrome and drug reaction with eosinophilia and systemic symptoms (DRESS), which have been reported in at least seven and three cases (US data only), respectively, none of which resulted in death. [22][23][24] Other adverse side effects include somnolence, respiratory tract infections, dizziness, and movement disorders. 2 Regarding ZIPR stability in whole blood, a prior study by Saar et al found near complete degradation in preserved antemortem human whole blood stored at 20 C after 20 weeks.…”
mentioning
confidence: 99%